PERSEPSI GURU PAI TERHADAP PEMANFAATAN ARTIFICIAL INTELLIGENCE SEBAGAI MEDIA ASESMEN FORMATIF - Chairul Amriyah; Akbar Rahman; Ahmad Saeful Ahyar; Ayub Kumalla; Darul Mustofa (STKIP Pesisir Selatan, 2026)
The development of Artificial Intelligence (AI) has significantly influenced various aspects of education, including formative assessment practices. AI enables teachers to receive assistance in designing assessment instruments, analyzing learning outcomes, and providing feedback more efficiently. This study aims to analyze Islamic Education teachers' perceptions of the use of Artificial Intelligence as a formative assessment tool. A qualitative descriptive approach was employed in this study. The participants consisted of ten Islamic Education teachers selected through purposive sampling. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that Islamic Education teachers generally have positive perceptions regarding the use of AI in formative assessment. AI is considered helpful in developing assessment instruments, generating diverse assessment items, accelerating learning outcome analysis, and supporting feedback provision. However, several challenges remain, including limited digital competence among teachers, concerns about the accuracy of AI-generated information, and ethical issues related to its implementation. Therefore, improving teachers’ digital literacy and providing AI-related training are necessary to optimize the use of AI in educational assessment.